GE_GERICHTE C/6390/2013 vom 26. Januar 2015 - GE Cour de justice (2015)
BAIL À LOYER; SOUS-LOCATION; ILLICÉITÉ; CONTESTATION DU CONGÉ; RÉSILIATION ABUSIVE; PROLONGATION DU BAIL À LOYER | CO.257f.3; CO.262; CO.272.1